BADANIE CODZIENNEGO CZASU SZKOLNEGO NAUCZYCIELI – NAMYSŁ NAD WŁASNĄ PRAKTYKĄ BADAŃ FENOMENOGRAFICZNYCH - Korzeniecka-Bondar, Alicja (Rocznik Pedagogiczny, 2018)
School is a complex system, inseparable from the specific context of here and now. Each day in- volves immersing in the course of particular events which are the result of multiple interactions at school. Time is what binds all the events taking place at school, and the category of time makes multi-level and multi-aspect analysis of school reality possible. The aim of the article is to reflect on the author’s own practice of phenomenographic studies of daily school time, to show the doubts occurring as part of the studies and to present the decisions taken. The text is the analysis of key elements of planning the studies, carrying them out and analyzing the results.